2011
DOI: 10.3109/02688697.2011.626879
|View full text |Cite
|
Sign up to set email alerts
|

Use of hyperbaric oxygen in traumatic brain injury: Retrospective analysis of data of 20 patients treated at a tertiary care centre

Abstract: Traumatic brain injury (TBI) related impact results in a permanent need for help in performing daily activities. Standard treatment consists of removing the cause, restore perfusion, support metabolic requirement and limit inflammatory and oxidative damage. Hyperbaric oxygen therapy (HBOT) is one such newer promising treatment that enhances neurological recovery to some extent. HBOT is intermittent inhalation of 100% oxygen at greater than normal atmospheric pressure and is internationally accepted for its rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…More extensive evidence from an early systematic review deemed HBOT’s therapeutic benefit inconclusive [58]. Yet, a recent retrospective study found TBI patients treated with HBOT have improved outcomes when compared to control counterparts [59]. Additionally, prospective studies administering HBOT after patients’ conditions stabilized also demonstrated improved outcomes based on GCS and GOS [60].…”
Section: Prophylactic Hypothermia and Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 99%
“…More extensive evidence from an early systematic review deemed HBOT’s therapeutic benefit inconclusive [58]. Yet, a recent retrospective study found TBI patients treated with HBOT have improved outcomes when compared to control counterparts [59]. Additionally, prospective studies administering HBOT after patients’ conditions stabilized also demonstrated improved outcomes based on GCS and GOS [60].…”
Section: Prophylactic Hypothermia and Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 99%
“…A retrospective study of 20 HBO-treated and 20 no HBOT subacute/chronic TBI patients (1–6 months after injury) demonstrated a greater improvement in the HBO-treated patients, particularly those who were the most impaired. 64 Two football players injured during play and diagnosed with TBI (or repetitive TBIs known as chronic traumatic encephalopathy) showed improved symptoms following HBOT. 65 However, since there were only two cases that also exhibited differences in age (15 and early 50s) and injury durations (3 months and 30 odd years), this evidence was really anecdotal at best.…”
Section: Does Hbot Improve Tbi and Ptsd Symptoms?mentioning
confidence: 99%
“…As with other therapies for TBI, there is limited evidence for its use in children after TBI. In a retrospective chart review in which three individuals under age 18 were included, there was significant recovery in individuals with persistent vegetative state, as measured by GCS, Rancho scores, and disability rating scale scores [64]. A larger clinical trial that included adolescents as young as 12 years showed significant improvements in post-TBI symptoms [65].…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%